Ethnic Concentration and Bank Use in Immigrant Communities. (1st April 2013) - Bohn, Sarah; Pearlman, Sarah
Abstract : Despite the many benefits of bank use, large portions of the U.S. population remain unbanked. One of the largest is immigrants, where the incidence of being unbanked is over 13% higher than among natives in 2001. We document growth in the nativity gap in bank use over time. We also test the importance of immigrant enclaves, defined as areas with high concentrations of immigrants from the same region, in explaining the increasing differential in bank use. Combining data from the Survey of Income and Program Participation, Census, and FDIC we find that immigrants living in enclaves are significantly less likely to have a bank account. We take steps to isolate one particular channel through which this might operate: the use of informal financial services provided by co‐ethnics in enclaves. The results suggest that demand‐side preferences may have power in explaining the persistence of the nativity gap in bank use in the United States.